Starch Evolution and Recent Advances - Ochubiojo Emeje, Martins (Biochemistry, 2022)
Starch - Evolution and Recent Advances is about the historical, scientific, and technological journey of starch so far, taking into account its traditional roles, uses, and applications as well as the most recent advances in the study of this unique polymer. It is a collective endeavor by a group of editors and authors with a wealth of experience and expertise in research and development, teaching, and quality control and public health. Chapters address such topics as the history, evolution, and health benefits of starch, advances in starch and starch product technology, the application of starch and starch-based polymeric materials in nanotechnology and environmental remediation, and much more.